INVESTIGATION OF THE CARRYING CAPACITY OF REINFORCED CONCRETE SLABS WITH CRACKS AFTER THEIR REINFORCEMENT WITH COMPOSITE FABRICS BY THE FINITE ELEMENT METHOD USING THE PRINS COMPUTER COMPLEX - V. P. Agapov; K. R. Aydemirov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The finite element method for cracked reinforced concrete slabs analysis after they were reinforced with composite fabrics in order to determine the residual safety factor is considered. Method. The method is based on the use of algorithms for calculating of structures with the account of the geometrical and physical nonlinearities, implemented in the PRINS program. These algorithms assume the use of the same calculation scheme in the process of the problem solving. However, the specifics of the assigned problem is that the design sсheme of the structure before the appearance of defects in it and after its amplification with the help of composite materials should change. Result. Taking into account this circumstance, the algorithms of nonlinear calculation of structures under the PRINS program were supplemented with an option that allows changing the parameters of the design scheme in the process of through calculation. To study the bearing capacity of reinforced concrete slabs, multilayer finite elements are used, for each of which a specific package of materials is specified. Modernization of the design scheme in this case comes down to replacing one package of materials with another. An example of calculation of a slab with a crack reinforced with composite fabric is given. Conclusion. It is shown that the use of a tunable design scheme can significantly improve the accuracy of calculations. In this case, the final result depends on what stage of the formation of defects in the slab its strengthening is realized. The special  multilayered finite elements of a quadrangular shape are used in calculations. The elements consist of four simple triangles, for which most of the matrix characteristics are calculated in a closed form. This is especially important when carrying out nonlinear calculations that require repeated computations of these characteristics.